Predictors of first-line treatment persistence in a Portuguese cohort of relapsing-remitting multiple sclerosis - Correia, I (2017)
Treatment persistence in first-line injectable disease-modifying therapies (DMT) for relapsing-remitting multiple sclerosis (RRMS) is an important indicator of effectiveness. Identifying predictors of treatment discontinuation is important as there are other therapies currently available and a growing range of emerging drugs. We report a retrospective study of RRMS and clinically isolated syndrome patients followed in a University Hospital during a 13-year period with the objective of identifying predictors of treatment persistence. An evaluation of persistence on the first DMT, rates of DMT discontinuation, and reasons and predictors of discontinuation was performed. A total of 410 patients were included, 69% female, with mean disease duration of 37.8months, mean age of 34.2years and mean follow-up time of 6.1years. The first DMT was glatiramer acetate (GA) in 27.56% of patients, interferon (IFN) β-1a intramuscular in 26.34%, IFNβ-1b in 26.10%, IFNβ-1a22 in 13.66% and IFNβ-1a44 in 6.34%. Treatment was discontinued in 16.34% of patients after 1year of treatment and in 50.24% of patients in the total follow-up time, with a mean time for discontinuation of 39.80months. Higher baseline Expanded Disability Status Scale score was an independent predictor of treatment discontinuation (hazard ratio 1.35, p=0.002). After the first year, treatment persistence was 90.74% for IFNβ-1a-IM, 88.46% for IFNβ-1a44, 83.18% for IFNβ-1b, 83.19% for GA and 69.64% for IFNβ-1a22 (p=0.014). Lower frequency of administration was associated with higher persistence rates. The most common reason for treatment discontinuation was lack of efficacy in all DMT subgroups.